Effect of Green Organizational Culture and Green Supply Chain on Company Performance With Profitability as Moderation - Istriari Istriari; Etty Murwaningsari (Quantitative Economics and Management Studies, 2023)
This study aims to examine the relationship between the influence of Green Organizational Culture and green supply chain management on company performance by adding profitability as a moderating variable. Green Culture Green organizations and supply chains are believed to provide efficiency and innovation in the company's operating processes. The research population is companies that publish sustainability reports for 2020-2021 in a row or not as many as 369 companies. Sampling in this study as many as 112 companies through a purposive sampling method. The test is carried out with Ordinary Least Square with the fulfillment of classical assumption tests including error normality, multicollinearity, heteroscedasticity, and heteroscedasticity tests. The results of this study indicate the relationship between the positive influence of organizational green culture on company performance and profitability strengthens the positive influence of organizational green culture on company performance. This is because the green culture of the organization requires employees to work effectively and efficiently to reduce the impact of major losses on the environment so that the company's goals are expected to be achieved. While the green supply chain shows that there is no positive effect on company performance. Profitability is not able to positively strengthen the influence of green supply chains on company performance because innovation is needed in its implementation.